2007
DOI: 10.1152/japplphysiol.00002.2006
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of end-expiratory recruitment with increased respiratory rate after saline-lavage lung injury

Abstract: Cyclical recruitment of atelectasis with each breath is thought to contribute to ventilator-associated lung injury. Extrinsic positive end-expiratory pressure (PEEPe) can maintain alveolar recruitment at end exhalation, but PEEPe depresses cardiac output and increases overdistension. Short exhalation times can also maintain end-expiratory recruitment, but if the mechanism of this recruitment is generation of intrinsic PEEP (PEEPi), there would be little advantage compared with PEEPe. In seven New Zealand White… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 72 publications
(85 reference statements)
1
25
3
Order By: Relevance
“…In comparison, our simulations show a much smoother transitions of PaO 2 after the onset of inspiration (expiration), without reaching a ''plateau'' before the onset of the following expiration (inspiration), in agreement with the findings of Baumgardner et al 3 The model of lung mechanics adopted in this study was not capable of generating intrinsic PEEP (except for very high respiratory rates). However, this did not prevent a satisfactory simulation of the experimental results and is in accordance with the findings of Syring et al 17 of a lack of intrinsic PEEP generation in a rabbit model very similar to that considered for our study, supporting their final suggestions that ''another mechanism, distinct from intrinsic PEEP, plays a role in the dynamic behavior of atelectasis. ''…”
Section: Discussionsupporting
confidence: 90%
“…In comparison, our simulations show a much smoother transitions of PaO 2 after the onset of inspiration (expiration), without reaching a ''plateau'' before the onset of the following expiration (inspiration), in agreement with the findings of Baumgardner et al 3 The model of lung mechanics adopted in this study was not capable of generating intrinsic PEEP (except for very high respiratory rates). However, this did not prevent a satisfactory simulation of the experimental results and is in accordance with the findings of Syring et al 17 of a lack of intrinsic PEEP generation in a rabbit model very similar to that considered for our study, supporting their final suggestions that ''another mechanism, distinct from intrinsic PEEP, plays a role in the dynamic behavior of atelectasis. ''…”
Section: Discussionsupporting
confidence: 90%
“…Syring et al, for example, reported maximal Pao 2 oscillations in lavaged rabbits at an I:E ratio of 2:1, suggesting that in that model derecruitment was slightly faster than recruitment. The general principle that shortening exhalation times can prevent end-expiratory collapse without an increase in intrinsic PEEP, however, was also demonstrated in the study by Syringe et al (34), in that study by increasing RR. Other potential mechanisms of VILI that could accompany IRV, such as higher static stretch and higher mean airway pressures, possibly resulting in increased inflammation (35)(36)(37)(38), were not addressed in our study.…”
Section: Discussionmentioning
confidence: 63%
“…1, Table 3). Table 2 Comparison of tidal volumes (V T s), ventilator peak pressure (P peak ), ventilator plateau pressure (P plateau ), and inspired carbon dioxide concentration (FICO 2 ) between the dead space (DS) and non dead space (NDS) groups 15 …”
Section: Resultsmentioning
confidence: 99%